Structural Health Monitoring by Using Fiber Optic Sensors in Composite Materials - Kaman, Mete Onur; Yılmaz, Muhammed Ali; Aytimur, Gökhan; Altın, Enes; Erdem, Serkan (My University, 2022)
In this study, design and application of a structural health monitoring (SHM) in composite materials with fiber bragg grating (FBG) sensors are investigated. The designed structure consists of laminated composite material that was produced by vacuum infusion method. The composite specimen was obtained by embedding a FBG sensor between the 12-layer glass layers. Moreover, SHM of the produced composite material was achieved by obtaining the strain data from the sensor embedded in the composite material. Application was carried out by making the composite plate fixed support on one side and applying different loads to the specimen. Strain ratios of these loads are obtained and the results graphics are shown.
Keywords: Nanobilim ve Nanoteknoloji